Digital marketing and brand identity: The gap between theory and practice amid technological and ethical transformations - Elamine, Bengasmia Mohamed (The International tax journal, 2025)
Under the accelerating digital transformation, digital marketing has become a decisive factor in building brand identity and enhancing customer engagement. The success of brands no longer depends solely on product quality but on their ability to create customized and interactive digital experiences that meet consumer expectations, especially with the rise of younger generations (such as Generation Z) who seek transparency and authenticity. Data indicates that 74% of consumers prefer brands that interact with them via social media platforms, while digital experiences directly influence 68% of purchasing decisions. However, companies face a gap between traditional marketing theories (such as the AIDA model) and the practical complexities arising from the evolution of artificial intelligence and big data analytics, necessitating a re-evaluation of digital strategies to ensure the sustainability of brand identity. The study relied on a Systematic Literature Review to analyze 19 peer-reviewed scientific studies published between 2020 and 2025, focusing on research exploring the relationship between digital marketing and brand identity. Key findings highlighted that Small and Medium Enterprises (MSMEs) achieved a 90% increase in sales through platforms like Instagram and TikTok, thanks to interactive content and direct communication with customers.